Bloodstream Infection Due to Vancomycin-resistant Enterococcus Is Associated With Increased Mortality After Hematopoietic Cell Transplantation for Acute Leukemia and Myelodysplastic Syndrome: A Multicenter, Retrospective Cohort Study. (14th January 2019) - Papanicolaou, Genovefa A; Ustun, Celalettin; Young, Jo-Anne H; Chen, Min; Kim, Soyoung; Woo Ahn, Kwang; Komanduri, Krishna; Lindemans, Caroline; Auletta, Jeffery J; Riches, Marcie L; ,
Abstract: Background: We examined the impact of vancomycin-resistant Enterococcus (VRE) bloodstream infection (BSI) on outcomes of allogeneic hematopoietic cell transplantation (HCT) utilizing the Center for International Blood and Marrow Transplant Research database. Methods: Adult and pediatric patients (N = 7128) who underwent first HCT for acute leukemia or myelodysplastic syndrome from 2008 through 2012 were analyzed as 3 groups—VRE BSI, non-VRE BSI, without BSI—according to BSI status at 100 days (D100) after allogeneic HCT. Multivariable models examined the effect of VRE BSI for overall survival (OS) and nonrelapse mortality (NRM) at 1 year. Results: Of 7128 patients, 258 (3.2%) had VRE BSI, 2398 (33.6%) had non-VRE BSI, and 4472 (63%) had no BSI. The median time to VRE BSI and non-VRE BSI were D11 and D15, respectively. Compared with non-VRE BSI patients, VRE BSI patients were older, had advanced-stage acute leukemia, and received umbilical cord blood (UCB) allografts. In multivariable models, VRE BSI was associated with lower OS (relative risk [RR], 2.9;(99% confidence interval [CI], 2.2–3.7) and increased NRM (RR, 4.7; 99% CI, 3.6–6.2) ( P < .0001) for both. Other predictors for worse OS and increased NRM were non-VRE BSI, older age, advanced disease stage, UCB allograft, – mismatch, comorbidity index ≥3, and cytomegalovirus seropositivity ( P < .001 for all variables). Conclusions: VRE BSI is associated with lowest OS and highest NRM compared with patients without BSI or non-VRE BSI. Novel interventions that address the pathophysiology of VRE BSI have the potential of improving survival after HCT. Abstract : In this registry study, vancomycin-resistant Enterococcus (VRE) bloodstream infection (BSI) by day 100 after hematopoietic stem cell transplantation was associated with decreased 1-year survival ( P < .0001). VRE BSI increased risk of nonrelapse mortality by 4.7 fold and 2.7 fold compared with no BSI or non-VRE BSI, respectively.